The Effect Of Think Pair Share Teaching Model To The Reading Comprehension Of Grade Eleven Students Of SMK Swasta GKPS 2 Pematang Siantar On A Factual Report Text - Glorya Natalia Rohani Napitupulu; Mungkap Mangapul Siahaan; Siska Anggita Situmeang (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The objectives of the research is to find out the effect of think pair share teaching model to the reading comprehension of grade eleven students of SMK Swasta GKPS 2 Pematang Siantar on a factual report text. This research employed a quantitative method with a quasi experimental design method. The data was collected by using multiple choice. In the experimental class the treatment used was think pair share teaching model, while the control class used question answer technique. The instrument used to collect data was taken from the result of the students’ pre-test and post-test scores which were then calculated. The results of the students’ scores on the post-test showed that the use of think pair share was very effective in reading comprehension on a factual report text of grade eleven students. T-test calculation shows that the t-test value is higher than the t-table value. The null hypothesis (H0) is rejected. And alternative hypothesis (Ha) is accepted. So, it can be concluded that the think pair share teaching model is very significant in developing students’ reading comprehension especially on factual report text.